Pelatihan Pencatatan Laporan Keuangan Berbasis Digital Bagi Kelompok Tani Desa Kayu Manis - Twenty Mariza Syafitri; Sri Wulandari; Rike Purnama Sari; Hafiz Nurkholis (Universitas Dehasen Bengkulu, 2023)
The current Digital Era requires people to be able to master and operate technology. This also applies to farmer groups. Farmers Groups are expected to be able to make digital records and bookkeeping to produce accurate financial reports. The benefit of using the